Costochondral graft in growing patients with hemifacial microsomia case series: Long‐term results compared with non‐treated patients. (29th June 2020) - Meazzini, Maria Costanza; Battista, Valeria M.A.; Brusati, Roberto; Mazzoleni, Fabio; Biglioli, Federico; Autelitano, Luca
Abstract: Objective(s): The aim of this study was to evaluate the long‐term effectiveness of costochondral graft in hemifacial microsomia (HFM) type III patients. Settings and sample population: A sample of 10 patients affected by HFM type III treated during growth in the same Centre with costochondral graft (CCG patients group) is compared with a control group (CG) sample of 10 non‐treated patients affected by the same malformation in order to understand whether surgery during growth provides advantages in terms of bony and facial symmetry after an 8‐year follow‐up. Materials and Methods: The growth of the CCG was assessed on panoramic X‐rays. To assess facial symmetry, a photometric evaluation on the frontal view was carried out. Results: In CCG patients group the graft grown in mean less than the healthy ramus, a good facial symmetry was achieved after surgery, but was lost in the majority of the cases at the most recent control. In CG, occlusal canting slightly increased and facial asymmetry was relatively stable during the years. Conclusion: In patients with a congenital deformity, restoring the height of the ramus leads to an immediate restitution of facial symmetry, but in the long term, there is a return to the asymmetrical pattern. In CG, the asymmetry is stable during years with no increase of the facial deformity.